Chronic myeloid leukemia in childhood: a case report - Uma Bhatta; Dosti Regmi (Journal of Pathology of Nepal)
Chronic myeloid leukemia is a rare hematological malignancy in the pediatric age group. It is a clonal hematopoietic stem cell disorder in which granulocytes are the major proliferative components with the presence of the BCR-ABL1 fusion gene. Here, we report a case of CML in a three - year child with a clinical presentation of fever and abdominal distension. The diagnosis was made based on bone marrow aspiration findings and molecular study.